2003
DOI: 10.2337/diacare.26.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Injectable or Implantable Progestin-Only Contraceptives on Insulin-Glucose Metabolism and Diabetes Risk

Abstract: Progestin-only contraceptives administered by injection (Depo-Provera) or subcutaneous implant (Norplant) have been available to U.S. women for about a decade. Two epidemiological studies found their use associated with increased incidence of type 2 diabetes. In reviewing publications relating progestin injections and implants to glucose metabolism, 25 studies of various study designs and laboratory methods were identified that reported at least one insulin value in nondiabetic women. Research subjects were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 60 publications
5
48
0
3
Order By: Relevance
“…Recent studies have shown a correlation between high progesterone levels and glucose intolerance (14,(16)(17)(18)(19)(20)(21)(22)(23). Exogenous progesterone decreases insulin sensitivity with the subsequent development of hyperglycemia in rodents (14,20), and the use of 17-OHPC to prevent recurrent preterm delivery is associated with an increased risk of developing glucose intolerance and gestational diabetes mellitus in humans (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a correlation between high progesterone levels and glucose intolerance (14,(16)(17)(18)(19)(20)(21)(22)(23). Exogenous progesterone decreases insulin sensitivity with the subsequent development of hyperglycemia in rodents (14,20), and the use of 17-OHPC to prevent recurrent preterm delivery is associated with an increased risk of developing glucose intolerance and gestational diabetes mellitus in humans (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that medroxyprogesterone may have deleterious effects on glucose metabolism and diabetes incidence [3,4]. For example, a study of Navajo women who used depot medroxyprogesterone intramuscularly found that users were more likely to develop diabetes than patients who had used any type of oral combination oestrogen-progestin contraception (odds ratio=3.8, 95% CI 1.8-7.9) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, progesterone is one of the candidates possibly implicated in the insulin resistance during pregnancy. Epidemiological studies have revealed that administration of progestin for contraceptive usage is associated with increased incidence of type 2 diabetes (13). A hyperglycemic hyperinsulinemic clamp study showed that progesterone administration for 8 wk reduced whole body glucose uptake in humans (13).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have revealed that administration of progestin for contraceptive usage is associated with increased incidence of type 2 diabetes (13). A hyperglycemic hyperinsulinemic clamp study showed that progesterone administration for 8 wk reduced whole body glucose uptake in humans (13). Concerning the role of progesterone in insulin secretion, female progesterone receptor knockout mice demonstrated a reduced fasting blood glucose level with elevation of serum insulin by increased ␤-cell proliferation (26), indicating the possible relation of progesterone with ␤-cell proliferation and/or function.…”
Section: Discussionmentioning
confidence: 99%